Why the EU needs to be a better neighbour to the Western Balkans: A geopolitical assessment - Philipp Lamprecht (FIW - Research Centre International Economics, 2025)
This FIW policy brief explores the negative effects of EU digital regulations on Western Balkan countries. It assesses how these countries have adapted to existing global data regulation models and explores potential avenues for boosting trade through the EU granting data adequacy status, aiming to reinforce regional ties and reduce the likelihood of these countries turning towards alternative global influences. It also examines the relationships between the EU and its neighboring countries in financial services, with a particular focus on trade finance. The brief discusses how the EU can improve trade finance access for these countries to facilitate financial integration with the EU and mitigate the risks of neighboring countries distancing themselves further from the EU. Ultimately, the aim of EU policies should be to strengthen ties with neighboring countries, seek partnerships to boost economic performance, and manage threats to security and peace. Accordingly, the EU needs to adapt its strategy in the Western Balkans and give the region greater geopolitical priority.
Keywords: 330